ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN ASURANSI SYARIAH TAHUN 2014-2017 - Muhammad Rafi; Muhamad Syaichu (Diponegoro Journal of Management, 2019)
This research aims to analyze the factors that influence the profitability of Islamic insurance companies in Indonesia. This study used firm size, volume of capital, asset tangibility, premium growth, and liquidity as independent variables and return on assets as the dependent variable.The number of samples in this research were 24 Islamic insurance companies that were determined by purposive sampling method. This study used secondary data from the financial statements of sharia insurance companies registered with the Financial Services Authority (OJK) in 2014-2017. The analytical method used in this study is multiple linear regression analysis where previously performed classical assumption that includes normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test.The results of this research showed that firm size and volume of capital have a positive and significant effect on return on assets. Tangibility assets have a negative and significant effect on return on assets. Premium growth and liquidity have a positive and insignificant effect on return on assets.